Spinal Dural Arteriovenous Fistulas: Clinical Experience with Endovascular Treatment as a Primary Therapy at 2 Academic Referral Centers - Joseph J. Gemmete; Neeraj Chaudhary; Augusto Elias; Ahmed K. Toma; Aditya S. Pandey; Robert A. Parker; Indran Davagnanam; Cormac O. Maher; Stefan Brew; Fergus Robertson (2013)
BACKGROUND AND PURPOSE: Spinal dural arteriovenous fistulas are a rare entity that, if left untreated, can lead to considerable morbidity with progressive spinal cord symptoms. The aim of this study was to evaluate the clinical outcome of patients with spinal dural arteriovenous fistulas that were primarily treated with endovascular embolization. MATERIALS AND METHODS: A retrospective review was performed of all patients from 1997–2010 who underwent treatment at 2 academic referral centers for a spinal dural arteriovenous fistula. Follow-up was performed by clinical examination, and functional status was measured by use of the Aminoff-Logue Disability Scale, McCormick classification grading, and mRS scores. The nonparametric Wilcoxon signed rank test was used to compare pretreatment and posttreatment Aminoff-Logue Disability Scale gait and micturition scores, McCormick classification grading, and mRS scores. P values < .05 were considered significant. RESULTS: A total of 38 patients were included. Five patients (2 endovascular, 3 surgical) were lost to follow-up and therefore were excluded from the analysis, 29 patients were initially treated from an endovascular approach (9 Onyx, 20 cyanoacrylate), and 4 patients were treated from a standard surgical approach. Five patients in the endovascular group subsequently underwent surgery for various reasons. The clinical improvements in the Aminoff-Logue Disability Scale gait and micturition scores, McCormick classification grading, and the mRS scores were statistically significant (P < .05, Wilcoxon signed rank test). CONCLUSIONS: We conclude that endovascular treatment of spinal dural arteriovenous fistulas can result in good clinical outcomes. Surgery remains the treatment of choice when safe embolization of the proximal radicular draining vein cannot be obtained or because the shunting artery of the spinal dural arteriovenous fistula also supplies the anterior spinal, posterior spinal, or a radiculomedullary artery.